Religious Franks : religion and power in the Frankish kingdoms - studies in honour of Mayke de Jong - Jong, Mayke De; Meens, Rob, 1959- (Manchester University Press, 2017)
A unique collection that offers fresh and original perspectives on some of the most important themes in Frankish history.